Tyrosine 9 is the key amino acid in microcin J25 superoxide overproduction - Chalon, Miriam Carolina (2009)
Escherichia coli microcin J25 (MccJ25) is a lasso-peptide antibiotic comprising 21 l-amino acid residues (G1-G-A-G-H5-V-P-E-Y- F10-V-G-I-G-T15-P-I-S-F-Y20-G). MccJ25 has two independent substrates: RNA-polymerase (RNAP) and the membrane respiratory chain. The latter is mediated by oxygen consumption inhibition together with an increase of superoxide production. In the present paper, the antibiotic MccJ25 was engineered by substituting Tyr9 or Tyr20 with phenylalanine. Both mutants were well transported into the cells and remained active on RNAP. Only the Y9F mutant lost the ability to overproduce superoxide and inhibit oxygen consumption. The last results confirm that the Tyr 9, and not Tyr20, is involved in the MccJ25 action on the respiratory chain target.